Restoration of heritage masonry buildings - L. Binda (Loggia, Arquitectura & Restauración, 1997)
Restoration of heritage masonry buildings was in the past, until the sixties, a job for a few experts. Damage to historic buildings due to earthquakes and decay due to lack of maintenance and ageing have now implicated a large number of architects and engineers in restoration design; as a consequence there is a great need for guidelines and codes for testing and application of various techniques for preservation as well as for training and teaching. On the following pages, the main recomendations, existing codes∫, development and future necessities are presented.